Case report: An OSAS patient with comorbid RLS/PLMS – a closer look at the causes of PAP intolerance - Dirks, Christina A. H.; Bachmann, Cornelius G. (Frontiers in Neurology, 2023)
Since 2017, hypoglossal nerve stimulation has been included in the S3-guidelines on restorative sleep/sleep disorders as an alternative treatment for patients with obstructive sleep related breathing disorders who cannot tolerate conventional PAP-therapy. Under certain conditions, some of these patients have the option to have a tongue pacemaker implanted during a surgical procedure to regain a restful night’s sleep. However, in some cases it does not solve the problem. In this case report, we present a patient who continued to have restless sleep despite implantation of a hypoglossus nerve stimulator. We provide a closer look at the underlying causes of PAP intolerance and emphasize the importance of a combined pneumological and neurological approach to sleep medicine in sleep-specific therapy evaluation.